2018
DOI: 10.1016/j.jmb.2017.12.013
|View full text |Cite|
|
Sign up to set email alerts
|

Single-Molecule Fluorescence Reveals the Oligomerization and Folding Steps Driving the Prion-like Behavior of ASC

Abstract: Single-molecule fluorescence has the unique ability to quantify small oligomers and track conformational changes at a single-protein level. Here we tackled one of the most extreme protein behaviors, found recently in an inflammation pathway. Upon danger recognition in the cytosol, NLRP3 recruits its signaling adaptor, ASC. ASC start polymerizing in a prion-like manner and the system goes in "overdrive" by producing a single micron-sized "speck." By precisely controlling protein expression levels in an in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 51 publications
5
37
0
Order By: Relevance
“…71 human proteins were cloned for expression as GFP-fusions in a cell-free expression system based on the eukaryotic organism of Leishmania tarentolae (LTE). This system produces full-length proteins up to 200 kDa with minimal truncations, minimal protein aggregation [36] and was previously used by our group to study the behaviour of various apoptotic proteins such as MyD88 [37], MAL [38] or ASC and NLRP3 [39].…”
Section: An In-vitro Protease Assay Identifies Targets Of Sars-cov2 Pmentioning
confidence: 99%
“…71 human proteins were cloned for expression as GFP-fusions in a cell-free expression system based on the eukaryotic organism of Leishmania tarentolae (LTE). This system produces full-length proteins up to 200 kDa with minimal truncations, minimal protein aggregation [36] and was previously used by our group to study the behaviour of various apoptotic proteins such as MyD88 [37], MAL [38] or ASC and NLRP3 [39].…”
Section: An In-vitro Protease Assay Identifies Targets Of Sars-cov2 Pmentioning
confidence: 99%
“…By controlling the concentration of DNA priming the system, we can tune the final expression levels of proteins and coexpress proteins at controlled ratios. We have tested this combination on a variety of biological systems over the years, and demonstrated that the flexibility of cell-free protein expression is a great asset to study protein aggregation and prion-like fibrillation 15,[18][19][20][21] .…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the size of the oligomers and assemblies more precisely, we used Photon Counting Histograms (PCH) analysis to determine the stoichiometry of the complexes. We have described the PCH method in detail in previous publications 15,19,22 , and will provide a brief description here of the principle and analysis. To perform Photon Counting, the sample (expressed at the highest DNA loading) is diluted so that individual peaks can be fully resolved.…”
Section: At Low Concentrations Both the Tir And Death Domains Are Rementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, both chaperones appear to play an active role in protein folding instead of just shielding unfolded protein from aggregating. Gambin and coworkers used single-molecule fluorescence microscopy to investigate polymerization of ASC, a protein involved in inflammation signaling [23]. They observed that ASC alone can polymerize into a fibril-like structure in a high ASC concentration.…”
mentioning
confidence: 99%